Gentamicin-Impregnated Collagen Sponge: Effectiveness in Preventing Sternal Wound Infection in High-Risk Cardiac Surgery - Filippo Rapetto; Vito D. Bruno; Gustavo Guida; Roberto Marsico; Pierpaolo Chivasso; Carlo Zebele (AboutScience Srl, 2016)
Sternal wound infections represent one of the most frequent complications after cardiac surgery and are associated with high postoperative mortality. Several preventive methods have been introduced, and recently, gentamicin-impregnated collagen sponges (GICSs) have shown a promising effect in reducing the incidence of this type of complications. Gentamicin is an aminoglycoside antibiotic that has been widely used to treat infections caused by multiresistant bacteria; despite its effectiveness, its systemic use carries a risk of toxicity. GICSs appear to overcome this side effect, topically delivering high antibiotic concentrations to the wound and thus reducing the toxic-related events. Although several retrospective analyses and randomized controlled trials have studied the use of GICSs in cardiac surgery, conclusions regarding their efficacy in preventing sternal wound infection are inconsistent. We have reviewed the current literature focusing on high-risk patients.